Sosialisasi Pencatatan Keuangan Melalui Pembukuan Sederhana Untuk Menunjang Perkembangan Bisnis Bagi Para Pelaku UMKM Di Kelurahan Blitar - Clariska Oktania Mega Saputri; Della Aulia Riskha Arifinda; Yuniningsih Yuniningsih; Rahman Amrullah Suwaidi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Recording of financial reports is a form of bookkeeping both manually and digitally for all financial activities in every business that is being carried out. Bookkeeping is the recording of financial transactions carried out during the business. Recording of financial reports is very important for MSME actors. One of the benefits of recording financial statements through simple bookkeeping for MSMEs is being able to find out the progress of the business or business being run so that they can control the costs incurred in operating the business and can find out the profit or loss earned while the business is running. The method used in this activity is the counseling method which is contained in socialization activities regarding procedures for recording financial reports through simple bookkeeping for MSMEs. The result of this activity is to provide new insights and knowledge for MSME actors in the Blitar Village regarding the importance of recording financial reports through simple bookkeeping and the stages in carrying out simple bookkeeping. After holding this socialization activity, it is hoped that it can provide benefits for MSME actors in the Blitar Village to make financial recording reports so that they can minimize losses in the businesses they run.